Insurance and behavioral economics improving decisions in the most misunderstood industry - Kunreuther, Howard. (Cambridge University Press, 2013)
"This book examines the behavior of individuals at risk, insurance industry decision makers and policy makers involved in the selling, buying, and regulating of insurance"--